2019
DOI: 10.3389/fped.2019.00460
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of β-Blockers on Postural Tachycardia Syndrome in Children and Adolescents: A Systematic Review and Meta-Analysis

Abstract: Background: Postural tachycardia syndrome (POTS) is a severe health problem in children. Short-term β-blockers are recommended for pharmaceutical treatment. However, there have been contradictory data about its efficacy among pediatric patients.Methods and Results: Eight studies comparing β-blockers to conventional treatments for children with POTS were selected, where 497 cases of pediatric POTS were included. The efficacy of β-blockers was evaluated using the effective rate, the change of symptom score, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Recently, intravenous metoprolol has been tested for use in the treatment of acute respiratory distress in acute COVID-19 and was found to improve oxygenation and reduce alveolar inflammation, shortening the duration of invasive mechanical ventilation overall [92]. Large-scale randomized evidence is eagerly awaited to confirm alleged pleiotropic anti-inflammatory effects of metoprolol [93] beyond its established safety, efficacy, and indications [94].…”
Section: Management Of Post-covid Dysautonomiamentioning
confidence: 99%
“…Recently, intravenous metoprolol has been tested for use in the treatment of acute respiratory distress in acute COVID-19 and was found to improve oxygenation and reduce alveolar inflammation, shortening the duration of invasive mechanical ventilation overall [92]. Large-scale randomized evidence is eagerly awaited to confirm alleged pleiotropic anti-inflammatory effects of metoprolol [93] beyond its established safety, efficacy, and indications [94].…”
Section: Management Of Post-covid Dysautonomiamentioning
confidence: 99%
“…Two other systematic reviews of POTS treatment have been recently published. 35,36 One 36 was based on somewhat different inclusion criteria in that no comparison or control group was required; it also included studies of nonpharmacologic interventions. A total of 28 published studies was included, and interventions were, in general, associated with "improvement," even though the measures of improvement were incompletely validated symptom scores.…”
Section: Discussionmentioning
confidence: 99%
“…36 Similar to the current systematic review, the study by Wells and colleagues identified the paucity of relevant studies. The other 35 recent systematic review focused on beta blocker use and included several studies that were published in Chinese and, thus, not captured by the English language search strategy of the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metoprolol exerts its therapeutic effect on POTS in children by inhibiting excessive sympathetic nerve function, decreasing HR, and the mechanical activation of ventricular wall baroreceptors, and inhibiting the effect of excessive plasm catecholamine content ( 7 – 10 ). However, the effective rate of metoprolol on POTS in children ranged from 57.1 to 57.89% ( 11 ). The main reason was that beta-adrenoceptor blockers could ameliorate the symptoms only for POTS children whose pathogenesis consisted of high catecholamine levels ( 11 ).…”
Section: Introductionmentioning
confidence: 99%